Maintenance from the Work Safety Point of View - Mészáros Zákányi, Renáta; Zákányi, Balázs; Tamás, Norbert (International Journal of Engineering and Management Sciences, 2021)
Deterioration of the technical condition of plant equipment is a common phenomenon nowadays. According to the experience of authorities, all this contributes to the occurrence of malfunctions and accidents. Plants that operate with an inadequate conservation strategy are now nearing the end of their design life, thus posing an increased accident risk. Aging processes are often accelerated by the operator’s underestimation of the effects of equipment stress and the extent of deterioration mechanisms, and the consequent inadequate design and operation of condition monitoring and maintenance procedures. The aim of our work is to examine trends in the light of modern maintenance optimization methods and, in connection with this, to make proposals for the optimization of maintenance scheduling for employers.